ANALYSIS OF WATER SUITABILITY FOR FLOATING NET CAGE (KJA) CULTIVATION OF TILAPIA (Oreochromis niloticus) IN GAJAH MUNGKUR RESERVOIR, WONOGIRI REGENCY, CENTRAL JAVA PROVINCE - Adian Wisnu; Eric Armando; Andri Nofreeana (Universitas Teuku Umar, 2025)
Reservoirs are one of the waters used for fishing activities. One of them is the Gajah Mungkur Reservoir which is used for cultivating tilapia using the KJA system. Activities around the reservoir can affect the quality of the water in it. The aim of this research is to determine the condition of reservoir water quality and to determine the suitability of reservoir waters for tilapia cultivation activities in the KJA system. The method used in this research is the matching and scoring method, which is then used to obtain the water suitability value. The ArcGIS application is also used to map and calculate the area that can be used for cultivation. The parameters measured are temperature, brightness, depth, current speed, basic substrate, pH, DO, CO₂,nitrate, ammonia, and phosphate. The suitability of the waters of the Gajah Mungkur Reservoir at 6 station points is divided into 3 classifications, namely, stations 1 and 2 are in the S3 category (marginally suitable), stations 3, 4 and 6 are in the S2 category (quite suitable) and station 5 is in the S1 category (very suitable). The scores obtained by each station are as follows: station 1 with a score of 34 (70.83%), station 2 with a score of 33 (68.75%), station 3 with a score of 37 (77.08%), station 4 with a score of 40 (83.33%), station 5 with a score of 43 (89.58%), and station 6 with a score of 39 (81.25%). The overall results show that the Gajah Mungkur Reservoir has a suitability value in the S2 category or is moderately suitable.